Digitizing zines: Spreading resistance discourses in the digital era - al Ramadhan, Muhammad Fakhran; Zufar, Biko Nabih Fikri; Papineau, Elise Imray (Center for Sociological Studies and Community Developmen, 2025)
Zines are grassroots publications that have long served as media of cultural and political resistance, traditionally circulated in material form within relatively small and tightly bound communities. With the advent of the internet, however, the scope and visibility of zines have expanded well beyond spatial and temporal boundaries, reducing production costs while simultaneously amplifying the reach of counter- hegemonic discourses. This study investigates how zines operate simultaneously as subject and as power within digital contexts, drawing conceptually on Michel Foucault’s theory of knowledge and power to frame the analysis. A mixed-methods design was employed, with 85 zines purposively selected from a population of 568 titles, determined through the Slovin formula with a 10% margin of error. Data were examined through a narrative approach, supported by AI-assisted text analysis, allowing for both qualitative interpretation and systematic computational support. The findings reveal that digital environments not only reinforce the omnipresence, omniscience, and omnipotence of resistance discourses but also transform the dynamics of knowledge production, positioning zines as effective vehicles for disseminating counter-discourses. By operating as both disseminators of resistance (subject) and as agents shaping collective truths (power), zines highlight the shifting relationship between grassroots media and structures of authority. Limitations and recommendations for future research are also discussed.